Case Series: Successful Resuscitation of Severe Facial Injuries Caused by a Chainsaw - Han Joo Choi (Journal of Trauma and Injury)
The treatment outcome remains poor of severe facial injuries because of the high risk of compromised airway or massive bleeding. We experienced two successful treatment cases of severe facial injury by the chainsaw. A 52-year-male had his face injured by the chainsaw during his work. He was transferred to the Level I trauma center using the Doctor-Helicopter. During his flight, bleeding control was tried and the information was given to the trauma surgeons before his arrival. His consciousness was alert and the vital signs were stable. The crushing wound, mandible open fracture, deep laceration of tongue, lip, neck and arterial bleeding were noted around his mandible. Nasotracheal intubation was performed under the bronchoscope-guided. Emergency operation (open reduction & internal fixation, primary repair with neurorrhaphy) was performed. At 30 hospital days, he was discharged with facial palsy on left mandibular area. A 30-year-male had his face injured by the chainsaw. He was transferred to our Level I trauma center from the local hospital. The deep-mutiple lacerations on right upper eyelid and forehead with the bony exposure were noted. The vital signs were stable and emergency operation was performed. He was discharged at 20 hospital days. Bone loss or tissue loss were not devastating than we expected even though the injury was occurred by the chainsaw. Aggressive treatment including airway manipulation or bleeding control and maximal opportunity of therapy are absolutely needed.